1972
DOI: 10.1002/apmc.1972.050270102
|View full text |Cite
|
Sign up to set email alerts
|

Polymerisationsenthalpie der ringöffnenden polymerisation von cyclopenten (CPE) zu trans‐polypentenamer (TPR)

Abstract: Für die Polymerisationsenthalpie der ringöffnenden Polymerisation von flüssigem Cyclopenten zu festem trans‐Polypentenamer (TPR) wurde ein Wert von 4,2 Kcal/Mol errechnet; für die Polymerisation des flüssigen Cyclopentens zu festem cis‐Polypentenamer ergibt die Berechnung eine Wert von 3,2 Kcal/Mol. Der kalorimetrisch bestimmte Wert von 4,5 Kcal/Mol für die Polymerisation von Cyclopenten zu trans‐Polypentenamer mit einem trans‐Gehalt von 65% stimmt mit den berechneten Werten gut überein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…À4.5 kcal mol À1 was reported for polypentenamers containing 65% trans double bonds. 5 Similar data were reported later by Lebedev. 6 The thermodynamic study using WCl 6 /Al(C 2 H 5 )Cl 2 catalysts revealed that the cyclopentene conversion does not depend on the catalyst activity but the reaction temperature.…”
Section: Introductionsupporting
confidence: 83%
“…À4.5 kcal mol À1 was reported for polypentenamers containing 65% trans double bonds. 5 Similar data were reported later by Lebedev. 6 The thermodynamic study using WCl 6 /Al(C 2 H 5 )Cl 2 catalysts revealed that the cyclopentene conversion does not depend on the catalyst activity but the reaction temperature.…”
Section: Introductionsupporting
confidence: 83%
“…Considering the similar ring strain energies of CPD and CP , it was assumed that these two compounds should maintain similar thermodynamic properties in ROMP/ROCM reactions (Table ) ,. As expected for an equilibrium polymerization (e. g. ROMP of CP) using either Grubbs or WCl 6 /Al(C 2 H 5 )Cl 2 catalysts, the monomer equilibrium concentration is not affected by the catalyst activity but the reaction temperature ,…”
Section: Introductionsupporting
confidence: 58%
“…Interestingly, polymerization to cis-polypentenamers had the smallest enthalpy change (∼−3.2 kcal mol −1 ), while the enthalpy changes of polymerization to 100% and 65% transpolypentenamer were found to be ∼−4.2 and ∼−4.5 kcal mol −1 , respectively (Table 1). 54 This difference in the enthalpy change of polymerization could be attributed to the relatively higher stability of the trans-alkene compared to its cis counterpart. The mechanism of depolymerization of polypentenamers was investigated by Korshak et al 55 and Badamshina et al 56 via the study of molecular weight and molecular weight distribution profiles over the course of depolymerization and will be discussed in Section 5.…”
Section: Depolymerizable Romp Polymersmentioning
confidence: 99%